2023
DOI: 10.1590/0103-8478cr20220096
|View full text |Cite
|
Sign up to set email alerts
|

The impact of agricultural comprehensive development on agro-ecological efficiency of China - evidence from perspective of scale and structure

Abstract: Promoting the agricultural sustainable development is one of the core objectives of agricultural comprehensive development (ACD), and the core of agricultural sustainable development lies in enhancing agro-ecological efficiency (AEE). Based on inter-provincial panel data from 2003-2017, the AEE was measured by a unexpected super-efficient SBM model. From the perspective of investment scale and investment structure, the impact of investment scale in ACD on AEE was examined using a panel econometric model, then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…The main factors affecting the improvement in China's livestock industry competitiveness include market price, production cost, technology level, resource conditions, processing capacity, quality and safety, trade barriers, and policy support, and studies have suggested that multiple measures be taken to sustain efforts to fast-track the improvement in the international competitiveness of the livestock industry [39][40][41][42]. Other studies have considered the characteristics of the high-quality development of the industry [43][44][45] and systematically explored the challenges and practical paths for accelerating development [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…The main factors affecting the improvement in China's livestock industry competitiveness include market price, production cost, technology level, resource conditions, processing capacity, quality and safety, trade barriers, and policy support, and studies have suggested that multiple measures be taken to sustain efforts to fast-track the improvement in the international competitiveness of the livestock industry [39][40][41][42]. Other studies have considered the characteristics of the high-quality development of the industry [43][44][45] and systematically explored the challenges and practical paths for accelerating development [46][47][48].…”
Section: Introductionmentioning
confidence: 99%